Understanding conversation around technology use in casual-social settings - Porcheron, Martin (2019)
Technologies such as smartphones have had a profound impact on everyday activities, providing us with instant access to a boundless archive of information and real-time communications with others. Additionally, new devices such as standalone 'smartspeaker' devices, which are controlled entirely through voice, are making an appearance in the home. This instantaneity and pervasiveness of these technologies has not unfolded without critique, however, as many complain of situations where we are surrounded by friends but become distracted, lose track of the conversation, or have trouble balancing demands both from our devices and the conversational involvement.